Diverse spaces of childhood and youth gender and other socio-cultural differences - Evans, Ruth; Holt, Louise (Routledge/Taylor & Francis Group, 2014)
'Diverse Spaces of Childhood and Youth' focuses on the diverse spaces and discourses of children and youth globally. The chapters explore the influence of gender, age and other socio-cultural differences, such as race, ethnicity and migration trajectories, on the everyday lives of children and youth in a range of international contexts.